2006
DOI: 10.21083/partnership.v1i1.110
|View full text |Cite
|
Sign up to set email alerts
|

Open Access Initiatives in India - an Evaluation

Abstract: Developing countries have embraced open access with a view to promoting visibility of research done in these regions. Open access initiatives described in this paper are based on interviews with information professionals responsible for creation and maintenance of online research repositories in India. Open access journals, e-print archives and e-theses repositories are covered with an emphasis on the sciences including the physical sciences, mathematics and the biomedical sciences. Existing repositories were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…One of the important research papers was by Fernandez (2006), who evaluated the growth and development of online research repositories in India within the broader framework of open access. She conducted interviews with information professionals responsible for the creation and maintenance of online research repositories in India.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…One of the important research papers was by Fernandez (2006), who evaluated the growth and development of online research repositories in India within the broader framework of open access. She conducted interviews with information professionals responsible for the creation and maintenance of online research repositories in India.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Vidyanidhi of University of Mysore is an example of document type specific collection that stores and provides access to theses and dissertations (Cross institutional ETD repository). Vidyanidhi accepts any thesis or dissertation that has been accepted in any of the Indian universities or institutions (Fernandez, 2006).…”
Section: Indian Scenariomentioning
confidence: 99%
“…Das et al (2005) found that problems of existing repositories in India are mainly due to limited availability of web servers running IRs. Fernandez (2006) found that universities in India are at present lacking in infrastructure for establishing IRs.…”
Section: Lht 281mentioning
confidence: 99%